International legal aspects of the matrimonial relations - Aliyeva, L.R. (Вестник Карагандинского университета, 2016)
This article is devoted to features of consideration of the family and marriage relations in the international private law. The main problems arising in the family and marriage relations with a foreign participation are considered. The author analyzes the existing family legislation of the Republic of Kazakhstan on marriage, a matrimony and a family. The author nvestigates questions of the legal nature of marriage, the marriage relations and the family relations in the international private law. The various theoretical positions about considered legal relations are exposed to the analysis also in this article.
Keywords: International private law; family law; family legislation; marriage; family; foreign participation; legal regulation; marriage relations; family relations; restoration of violated rights; responsibility